Impact of Solid Rocket Propellant Grain Manufacturing Limitations on Launch Vehicle Capability - Krishnan, Anish B.; Thakur, Dineshsingh G. (Defence Science Journal, 2024)
It is examined if any limitations in existing solid rocket propellant grain manufacturing methods adversely affected the payload capability of recent space launch vehicles. It is seen if the transition from heavy, segmented metal rocket motor casings to lightweight monolith composite casings is possible without loss of ability to design and realize high-performance grain configurations using simple and safe methods. Considering payload fraction as the comparative performance metric, recently flown solid rocket-propelled, small-lift launch vehicles were surveyed and ranked. Solid rocket boosters of underperforming launch vehicles were investigated for manufacturing factors influencing payload fraction by comparing them to boosters of better-performing launch vehicles in their weight class. Relationships between payload fraction and the solid boosters’ mass fractions, casing construction, shape of thrust profile, propellant grain configuration and method employed to manufacture the grain were analysed. It is shown that those launch vehicles that did not possess or use the technology necessary to manufacture high-performance grain configurations like undercut finocyl in monolith composite casings ended up having boosters delivering poor thrust profiles with high inert mass ultimately leading to low payload fractions.